2014
DOI: 10.1186/1471-2164-15-553
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of callus from Picea balfouriana

Abstract: BackgroundPicea likiangensis var. balfouriana (Rehd. et Wils.) Hillier ex Slavin (also known as Picea balfouriana) is an ecologically and economically important conifer that grows rapidly under optimum conditions and produces high-quality wood. It has a wide geographic distribution and is prevalent in southwest and eastern regions of China. Under suboptimal conditions, P. balfouriana grows slowly, which restricts its cultivation. Somatic embryogenesis has been used in the mass propagation of commercial species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…Temperature should be an important factor controlling tree growth rates. Similar results were found on Western Sichuan Plateau (Duan et al, 2010;Li et al, 2014). Since tree growth was not limited by water condition, higher mean summer temperature could contribute to tree growth by stimulating photosynthesis.…”
Section: The Climatic Information Recorded In the Tree-ring Width Andsupporting
confidence: 82%
See 1 more Smart Citation
“…Temperature should be an important factor controlling tree growth rates. Similar results were found on Western Sichuan Plateau (Duan et al, 2010;Li et al, 2014). Since tree growth was not limited by water condition, higher mean summer temperature could contribute to tree growth by stimulating photosynthesis.…”
Section: The Climatic Information Recorded In the Tree-ring Width Andsupporting
confidence: 82%
“…In southwestern China, Chuanxi spruce (Picea balfouriana) plays a key role in environmental protection and wood production (Li et al, 2014). It is crucial to evaluate how spruce trees respond to C a increases and to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Information regarding the expression of AGP genes in in vitro embryogenesis is very scarce. Some studies have shown up-regulation of some AGP genes associated with the initiation of somatic embryogenesis in Picea balfouriana (Li et al, 2014b) and microspore embryogenesis in B. napus (Malik et al, 2007;El-Tantawy et al, 2013).…”
Section: Cell Wall Remodelling: Pectins and Agpsmentioning
confidence: 99%
“…Over the past few years, progress of molecular techniques have immensely contributed in understanding the molecular aspects of SE in many plant species i.e. Arabidopsis [ 5 , 6 ], cotton [ 7 ], alfalfa [ 8 ], conifer [ 9 ], potato [ 10 ], Glycine max [ 11 ], oil palm [ 12 , 13 ], maize [ 14 ], Picea glauca [ 15 ], P. balfouriana [ 16 ], Vitis vinifera [ 17 ], Medicago truncatula [ 18 ] and Manihot esculenta [ 19 , 20 ]. Although the draft molecular interaction network provided for SE highlights the potential interactions at a molecular level [ 21 ], the functional characterization of the majority of genes involved in somatic-to-embryogenic transition and subsequent embryo maturation still remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%